2020
DOI: 10.3390/min10090814
|View full text |Cite
|
Sign up to set email alerts
|

Metal Mobility in a Mine-Affected Floodplain

Abstract: The study attempted to map and predict the remobilization of metals in a floodplain which had been heavily affected by long-term Zn–Pb mining. This research, based on Zn, Cd, Pb, Ca and Fe speciation, mineralogy and the stratigraphy of sediments which had accumulated over the distance of a dozen or so km from the mine, revealed variable potential for metal mobilization. The results suggest that a drop in the water table, something to be expected after the closure of a mine, would be accompanied by a decrease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…Studies on metals such as cadmium (Cd), chromium (Cr), nickel (Ni), lead (Pb) and zinc (Zn) have shown that they affect soil biota and can accumulate in plants growing in the soils, potentially entering the human food chain [7][8][9]. Once metals enter the soil, they may migrate along the soil column and into the groundwater, thus affecting the environment [10,11]. Furthermore, soils in floodplains that have functioned as sinks for long periods can become sources of metals when conditions (such as pH) or processes (such as erosion and deposition) change [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on metals such as cadmium (Cd), chromium (Cr), nickel (Ni), lead (Pb) and zinc (Zn) have shown that they affect soil biota and can accumulate in plants growing in the soils, potentially entering the human food chain [7][8][9]. Once metals enter the soil, they may migrate along the soil column and into the groundwater, thus affecting the environment [10,11]. Furthermore, soils in floodplains that have functioned as sinks for long periods can become sources of metals when conditions (such as pH) or processes (such as erosion and deposition) change [12][13][14].…”
Section: Introductionmentioning
confidence: 99%